Exploring the Effects of Teachers’ Use of Nonviolent Communication on Learners’ Classroom Participation in the EFL Classroom - Ben-Yahia, Moad; Lamzira , Fatima Zahra (International Journal of Language and Literary Studies, 2024)
With communication being the backbone of language classes, the interactions learners have with each other and with their teachers play a chief role in the teaching-learning process in EFL classes. Accordingly, teachers and researchers are in constant search for various innovative ways in which they can increase the frequency and quality of learners’ classroom participation. Evidently, this is not an easy task, but using nonviolent communication (NVC) – an approach to communication that promotes mindfulness, empathy, mutual understanding and respect – seems to have a lot to offer in this respect. The use of NVC has led to positive effects in an array of domains. However, little is investigated with regard to its effects on classroom participation. Against this background, the aim of this study was to explore the effects of the teachers’ employment of NVC on learners’ classroom participation in EFL classes. An experimental design with systematic observation was implemented for the study, where the participants’ classroom participation was systematically observed and reported using a standardized observation protocol. The results indicated that the use of NVC in communicating with learners positively affects their classroom participation frequency.